EVALUASI KESIAPAN PEMERINTAH DAERAH DALAM MENERAPKAN PERATURAN PEMERINTAH NO. 71 TAHUN 2010 (STUDI KASUS PADA DINAS PEKERJAAN UMUM KABUPATEN MINAHASA UTARA) - Nugraha, Brian Taruna; Pangemanan, Sifrid; Walandouw, Stanley K. (ACCOUNTABILITY, 2015)
Changes in financial governance of the Republic of Indonesia has always been done by the government to increase the quality of management, financial accountability and transparency of the country to the fullest. This is evidenced by the issuance of government accounting standards based on Government Regulation 71 of 2010 on the application of accrual-based government accounting standards. Government Regulation No. 71 of 2010 which confirms that the adoption of accrual accounting is implemented at the latest by 2015. This would require careful preparation so that the implementation of accrual accounting can be done well. The object of this research is Department Of Public Works In North Minahasa District. Data analysis methods used in this study is a qualitative method. From the research, explained that Department Of Public Works In North Minahasa District is ready to accrual-based SAP implementation.